(untitled) (LEARNing Landscapes, 2011)
Over the past four years, teacher-based inquiry has played a central role in the Building Community Through Telecollaboration Project, which involves Quebec elementary school teachers in a community of practice focused on the integration of ICT-supported learning into the classroom. During the school year, the teachers met in four face-to-face meetings. Between these meetings, three Cycle Team Leaders facilitated ongoing collaboration using a variety of communication tools. Some of the questions that were addressed in the project and the results that were generated through its multi-organizational partnership are shared along with some of the major lessons learned.